Bridging agronomy and pharmacology the antidiabetic promise of Oldenlandia - Nor Isnaeni Dwi Arista; Yochidamai Akhsanitaqwim (Bioculture Journal, 2026)
Background: The growing global burden of diabetes and the limitations of current treatments require sustainable alternatives. This study aims to evaluate the potential of the weedy genus Oldenlandia as a novel, sustainable resource for diabetes management by synthesizing evidence from agronomy, phytochemistry, and pharmacology. Methods: A systematic literature review was conducted using major scientific databases. A multidisciplinary search strategy was employed, and the collected data were integrated using narrative synthesis. Findings: The analysis shows that Oldenlandia species are resilient plants requiring low agricultural inputs. They are rich in bioactive compounds like iridoids and flavonoids, and preclinical studies confirm significant antidiabetic effects, including lowered blood glucose and reduced inflammation via mechanisms such as AMPK-NF-κB pathway modulation. Conclusion: Oldenlandia presents a promising and sustainable candidate for developing new antidiabetic therapies, bridging traditional use with scientific validation. Novelty/Originality: This review offers a novel, integrated perspective that simultaneously evaluates the agronomic feasibility and pharmacological potential of a weed for diabetes treatment, a unique approach not commonly found in existing literature.